Teknik Pengolahan Limbah Agroindustri sebagai Pakan Alternatif untuk Ternak Ruminansia (Maco'ou : Jurnal Pengabdian Masyarakat, 2025)
The priority issue for ruminant farmers in Lampermai Village, Krueng Barona Jaya District, Aceh Besar Regency, is still the low ability to process animal feed. Therefore, this community service program aims to facilitate the transfer of knowledge and feed technology to enhance the capacity of farmers in providing quality feed. Based on the results of observations and interviews, it was found that farmers still use a system of providing green feed without paying attention to the appropriate nutritional content. The method of implementing the activities was carried out through socialization, technical training, and field assistance. The results of the activities also showed success in the production of fermented feed (silage) from local materials, such as rice straw and bran. This activity has a positive impact on feed management efficiency, particularly in the knowledge and skills of the farmers. Conclusion: This community service program successfully enhanced the capacity of farmers in processing and managing ruminant livestock feed. The application of simple technologies, such as silage production, can optimize the use of local materials and improve feeding efficiency.